2020
DOI: 10.3390/antibiotics9040193
|View full text |Cite
|
Sign up to set email alerts
|

Management of a Case of Peritonitis Due to Neisseria gonorrhoeae Infection Following Pelvic Inflammatory Disease (PID)

Abstract: Pelvic inflammatory disease (PID), a serious infection in sexually active women, is one of the reasons for which females seek care in emergency departments and therefore represents an important public health problem. PID is the result of an endocervical infection with different microorganisms, which then ascend to the endometrium and fallopian tubes. Symptoms of PID may be mild and aspecific, making its diagnosis difficult. However, this clinical condition requires effective antibiotic treatment to reduce inci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 12 publications
0
2
0
1
Order By: Relevance
“…A pesar de su alta prevalencia, hasta la fecha se han documentado microbiológicamente pocos casos de pelvi-peritonitis por N. gonorrhoeae [7][8][9][10] . Ello es debido a que los síntomas pueden ser leves e inespecíficos, presentándose como un abdomen agudo, con fiebre aunque con pruebas de imagenología normales, lo cual dificulta su diagnóstico.…”
Section: Discussionunclassified
“…A pesar de su alta prevalencia, hasta la fecha se han documentado microbiológicamente pocos casos de pelvi-peritonitis por N. gonorrhoeae [7][8][9][10] . Ello es debido a que los síntomas pueden ser leves e inespecíficos, presentándose como un abdomen agudo, con fiebre aunque con pruebas de imagenología normales, lo cual dificulta su diagnóstico.…”
Section: Discussionunclassified
“…Despite the small size of our study compared to other studies [ 16 , 17 , 18 , 24 ], it presents a unique opportunity to analyze unique aspects of gonorrhea in exposed “asymptomatic” women, a population that is understudied because these individuals do not seek treatment. While some infected women may spontaneously clear the infection over time, by remaining undiagnosed and untreated, many could develop severe disease (PID) and associated consequences such as infertility or ectopic pregnancies [ 38 , 39 , 40 , 41 ]. Therefore, along with a continuing focus on developing vaccination strategies, it is crucial to evaluate other preventative aspects to reduce the spread of N. gonorrhoeae and other STIs.…”
Section: Discussionmentioning
confidence: 99%
“…Salpingitis with a large right tubo-ovarian abscess (iii) IV ertapenem then oral amoxicillinclavulanic and metronidazole Pegg and Owen[16] 18(i) Recurrent abdominal pain and vomiting (ii) Clinical and plain radiological signs of gastrointestinal obstruction (i) Exploratory laparotomy, appendicectomy, adhesiolysis, and peritoneal lavage (ii) Peritoneal cavity contained 900 ml of strawcoloured fluid, widespread adhesions between adjacent loops of small bowel Two-day history of colicky abdominal pain, bile-stained emesis, and constipation (ii) CT abdomen showed dilated loops of small bowel and a small amount of free fluid within the pelvis (i) Laparotomy and adhesiolysis (ii) Multiple adhesions at terminal ileum (iii) Free peritoneal fluid and bilateral pyosalpinx (iv) Antibiotics Ahmed et al[9] 38 (i) One-day history of severe abdominal pain and three-week history of constipation (ii) CT abdomen and MRI-pelvic showed dilatation of the colon with transition point in the sigmoid colon. Multiple bilateral cystic lesions suspicious for abscesses (i) Conservative management (ii) Intrauterine device removed (iii) Doxycycline and ceftriaxone Francesco et al[17] 49 (i) One-day history of acute abdominal pain, febrile 38.5 °C (ii) Plain X-ray was normal (iii) CT abdomen showed dilated loops of proximal small bowel with wall thickening and an air-fluid level (i) Exploratory laparoscopy and peritoneal lavage (ii) Nonmalodorous pus in the pelvis with signs of peritonitis. The uterus was oedematous, erythematosus, and swollen (iii) Azithromycin and metronidazole Al-Ghassab et al[18] 32 (i) One-day history of obstructive symptoms (ii) Abdominal X-ray showed subacute SBO (iii) CT abdomen showed dilated loops of small bowel and left hydrosalpinx (i) Exploratory laparoscopy and adhesiolysis (ii) Multiple small bowel adhesions at the ileum and between the liver and anterior abdominal 3 Case Reports in Surgery…”
mentioning
confidence: 99%